Histopathology of Mekong Giant Catfish (Pangasianodon gigas) infected with columnaris bacteria in Chiang Mai province, Thailand - Maneepitaksanti, Worawit (Microscopy and Microanalysis Research – The Journal of The Microscopy Society of Thailand, 2019)
Mekong giant catfish (Pangasianodon gigas) is the largest herbivorous freshwater. This fish habits in the Mekong river area. Problems on the growth development and aquatic environment make the population of this fish decrease. Recently, the aquaculture of this fish was successful, thus raised this fish to economic fish for fishery production. However, a constraint in aquaculture is due to the infectious diseases. From the experiment of Mekong giant catfish in Chiang Mai province the high mortality of fish was taken out in cultured system. The present study, therefore, aimed to diagnose and demonstrate the causes of mortality and histology changes on moribund Mekong giant catfish. The moribund fish were observed the clinical signs, external parasite and histopathological changes by wet smear technique. The pathogen and histopathology of sections were examined and recorded by the trinocular compound microscope attached to the digital camera. The results showed creamy white or brown patches on the skin and fins of moribund fish with the high mortality rate (80%). Under the microscopic examination of skin, the hay stack of columnaris bacteria was found. Histopathology changes indicated epidermal ulceration, necrosis and severe dermal infiltration of neutrophils, numerous of culumnaris bacteria invasion, the gill hyperemia and oedema, degeneration of hepatocytes and hemorrhage in liver, necrotic degeneration and hemorrhage of spleen, hemorrhagic kidney degeneration. This study demonstrated that columnaris bacteria was the main pathogens for high mortality of Mekong giant catfish cultured in Chiang Mai province, Thailand.